Performance Evaluation of Different Twist Drills in Dry Drilling of AISI 304 Austenitic Stainless Steel - Caydas, Ulas; Hascalik, Ahmet; Buytoz, Omer; Meyveci, Ahmet (Taylor & Francis Inc, 2011)
This article evaluates the performances of HSS, K20 solid carbide, and TiN-coated HSS tools in dry drilling of AISI 304 austenitic stainless steel. The roles of spindle speed, feed rate, drill point angle, and number of holes on the surface roughness, tool flank wear, exit burr height, and enlargement of the hole size were experimentally investigated. The structure of this analysis has been determined by means of the technique called the design of experiments (DOE), which allows us to perform a relatively small number of experiments. An L-9 orthogonal array was used to collect the experimental data. The experimental results demonstrated that the above mentioned drilling performances showed a tendency to increase in response to the cutting parameters. TiN-coated HSS drill showed the highest performance with longer tool life and higher hole quality, as well as lower surface roughness, followed by the K20 carbide and the HSS tools.
Keywords: AISI 304; Burr formation; Dry drilling; Drill type; TiN-coating